Experimental characterization and component-based modeling of deck-to-pier connections for composite bridges. (November 2018) - Abbiati, Giuseppe; Cazzador, Enrico; Alessandri, Silvia; Bursi, Oreste S.; Paolacci, Fabrizio; De Santis, Stefano
Abstract: Higher stiffness and strength achieved with a reduced overall weight together with an extensive use of prefabrication justify the growing diffusion of Steel-Concrete Composite (SCC) bridges since the early 2000s, especially for the 20 ÷ 80 m span range. Former experimental campaigns aimed at investigating the static response of simply supported continuous composite decks subjected to gravity loads, highlighted deck-to-pier connections, which typically experience negative moments, as critical elements. More precisely, tensile stresses occurring in the concrete slab and compression of bottom flanges of steel girders may cause concrete cracking and steel buckling, respectively. The adoption of Concrete Cross Beams (CCBs) allows for circumventing such issues and represents an enhanced solution for deck-to-pier connections in SCC bridges with continuous deck. In detail, steel girder head plates provided with shear studs transfer compression and shear loads to the CCB whilst additional steel rebars bring tension forces coming from adjacent concrete slabs. Although deck-to-pier connection based on CCBs can be designed with the support of Eurocodes, guidelines are limited to vertical loads and no standard exist for design against earthquakes. In order to investigate the seismic response of deck-to-pier connections based on CCBs and provide relevant design guidelines, an extensive research program was developed within the European Project SEQBRI, which is summarized in this paper. Highlights: Three alternative solutions for deck-to-pier connections in composite bridges are developed. Monotonic and cyclic tests of proposed connections are carried out. The seismic performance of different connections between concrete cross beam and deck are favorable. Component-based models of proposed connections are conceived and validated up to failure. Developed models can be used within the performance-based earthquake engineering framework.